How can campus living labs thrive to reach sustainable solutions? - Annika Herth; Robert Verburg; Kornelis Blok (Cleaner Production Letters)
Many Higher Education Institutions utilize living labs to address complex societal challenges and foster innovative and sustainable solutions on campus. Despite the perceived benefits of campus environments for transdisciplinary real-world innovation, living labs often encounter challenges. As such, there is a growing need for more knowledge on facilitating these on-campus initiatives in different development phases. Here, enabling factors for on-campus living labs are investigated and their salience across the living labs’ development process established. First, a systematic literature review was conducted, identifying sixteen enabling factors. The most pertinent ones were stakeholders and networks, coordination on the organizational level, a conducive work culture, co-creation and collaboration, and suitable methods and practices for living labs. Second, all factors’ relevance across living labs’ development phases were assessed through the input of an expert panel. To that end, a mapping exercise was developed, which can in itself serve as a discussion tool for living lab practitioners. The results suggested that the initiation phase relies on leadership, coordination, stakeholder engagement, a conducive work culture, and funding. In contrast, operational phases were enabled by shared understanding, internal management, stakeholder collaboration, methodological appropriateness, and evaluation. Lastly, the dissemination phase hinged on transfer, scaling, evaluation, learning, and bridging stakeholders and contexts. These insights contribute to a better understanding of enabling factors for campus living labs during different phases of development, offering tailored guidance for stakeholders while stressing adaptability to local contexts. Subsequently, campus living labs may be better equipped to effectively generate sustainable solutions for the complex societal questions of this time.